What the Demolition of Public Housing Teaches Us about the Impact of Racial Threat on Political Behavior. Issue 1 (24th February 2015) - Enos, Ryan D.
Abstract : How does the context in which a person lives affect his or her political behavior? I exploit an event in which demographic context was exogenously changed, leading to a significant change in voters' behavior and demonstrating that voters react strongly to changes in an outgroup population. Between 2000 and 2004, the reconstruction of public housing in Chicago caused the displacement of over 25, 000 African Americans, many of whom had previously lived in close proximity to white voters. After the removal of their African American neighbors, the white voters' turnout dropped by over 10 percentage points. Consistent with psychological theories of racial threat, their change in behavior was a function of the size and proximity of the outgroup population. Proximity was also related to increased voting for conservative candidates. These findings strongly suggest that racial threat occurs because of attitude change rather than selection.